Cross and long-shore variations in reef fish assemblage structure and implications for biodiversity management. (5th March 2019) - Bach, Lydia L.; Saunders, Benjamin J.; Newman, Stephen J.; Holmes, Thomas H.; Harvey, Euan S.
Abstract: Fish communities are an important cultural, recreational and commercial resource that also have an important role in the functioning of marine ecosystems. Around the world fish assemblages are experiencing pressures from anthropogenic activities, and marine spatial planning is being established to mitigate these impacts and assist with biodiversity conservation. Information about how fish assemblages are structured across a range of spatial scales which encompass variations in physical, biotic and environmental parameters will assist marine spatial planning and management. We investigated differences in reef fish assemblage composition over three reef lines across an inshore to offshore gradient (3–23 m depth) at two marine reserves (70 km apart) in the Perth metropolitan region, Western Australia. There were significant increases in the number of individuals, species richness, and relative abundance of fish species across the shallow shelf depth gradient in the two locations. There were distinct fish assemblages associated with each reef line, correlated to depth and distance from shore. The differences across the shelf gradient, even over this small depth range, were greater than the differences between the two locations. These findings have implications for marine spatial management and the design of marine reserves that aim to conserve biodiversity. It may be most appropriate for such marine reserves to encompass a wide depth gradient, rather than a large longshore area. At the very least, cross and longshore patterns in fish assemblages should be taken into consideration and used to guide spatial management plans for biodiversity conservation. Highlights: Differences in fish assemblages were found across a shallow reef line depth gradient. Species richness and abundance increased from inshore to offshore reefs. Patterns in composition among reef lines were consistent among locations. Among reef line differences were greater than differences between locations. Marine reserves should encompass cross-shore variation for biodiversity conservation.